DNA Methylation Profiles in a Group of Workers Occupationally Exposed to Nanoparticles - Rossnerova, Andrea; Honkova, Katerina; Pelclova, Daniela; Zdimal, Vladimir; Hubacek, Jaroslav A; Chvojkova, Irena; Vrbova, Kristyna; Rossner, Pavel; Topinka, Jan; Vlckova, Stepanka; Fenclová, Zdeňka; Lischkova, Lucie; et al. (International journal of molecular sciences, 2020)
The risk of exposure to nanoparticles (NPs) has rapidly increased during the last decade due to the vast use of nanomaterials (NMs) in many areas of human life. Despite this fact, human biomonitoring studies focused on the effect of NP exposure on DNA alterations are still rare. Furthermore, there are virtually no epigenetic data available. In this study, we investigated global and gene-specific DNA methylation profiles in a group of 20 long-term (mean 14.5 years) exposed, nanocomposite, research workers and in 20 controls. Both groups were sampled twice/day (pre-shift and post-shift) in September 2018. We applied Infinium Methylation Assay, using the Infinium MethylationEPIC BeadChips with more than 850,000 CpG loci, for identification of the DNA methylation pattern in the studied groups. Aerosol exposure monitoring, including two nanosized fractions, was also performed as proof of acute NP exposure. The obtained array data showed significant differences in methylation between the exposed and control groups related to long-term exposure, specifically 341 CpG loci were hypomethylated and 364 hypermethylated. The most significant CpG differences were mainly detected in genes involved in lipid metabolism, the immune system, lung functions, signaling pathways, cancer development and xenobiotic detoxification. In contrast, short-term acute NP exposure was not accompanied by DNA methylation changes. In summary, long-term (years) exposure to NP is associated with DNA epigenetic alterations.
Keywords: Young Adult; DNA Methylation; Male; genom lidský; Occupational Exposure; mladý dospělý; metylace DNA; Nanoparticles; epigeneze genetická; nanočástice; pracovní expozice; Adult; Aged; dospělí; mužské pohlaví; senioři; nanokompozity; Genome, Human; Nanocomposites; lidé; ženské pohlaví; Humans; Female; lidé středního věku; Epigenesis, Genetic; Middle Aged